Edukasi “SiGap-Siaga Dan Tanggap” Menghadapi Resiko Bencana Gempa Bumi Megathrust Pada Remaja Di Nasyiatul Aisyiyah Kelurahan Pleret, Kulon Progo - Istiqomah Rosidah; Anita Setyowati (CV. Multi Kreasi Media, 2025)
Earthquakes are natural disasters that can occur suddenly. Although various early indicators or precursors have been studied extensively, there is still no technology capable of accurately predicting the exact time of an earthquake. Therefore, it is crucial for communities to gain knowledge and understanding about how to be prepared and responsive to the risks of earthquakes—particularly megathrust earthquakes, which pose a significant threat in high-risk areas such as the southern part of Java Island. Unfortunately, the role of the community—despite being the largest and most important group in disaster mitigation efforts—is often overlooked in disaster preparedness planning. Yet, preparedness is a critical component, as it can significantly reduce mortality rates caused by earthquakes. One effective way to improve preparedness is through educational programs such as “SiGap – Ready and Responsive,” aimed at adolescents. Adolescents, aged between 10 and 19, are in a unique developmental stage that is essential for building a strong foundation of health knowledge. Educating this age group is expected not only to foster proactive attitudes in disaster response but also to encourage sustained community involvement in preparedness activities. Choosing the right educational media also plays an important role in enhancing understanding, and digital media is one of the most effective tools. Utilizing engaging technology can help deliver information in a way that is easier to absorb and remember. Therefore, innovation is needed in delivering education to adolescents so that the intended messages are effectively communicated. To build a society that is well-prepared and responsive to the risks of megathrust earthquakes, an advanced and modern learning model tailored to the younger generation is essential. This study aims to assess the impact of the “SiGap – Ready and Responsive” educational program on adolescent preparedness in facing the threat of megathrust earthquakes, specifically among the youth of Nasyiatul Aisyiyah in Pleret, Kulon Progo.